Room-temperature spontaneous superradiance from single diamond nanocrystals - Carlo Bradac (Nature Portfolio, 2017)
Previously, superradiance was observed from sizeable crystals or close to liquid-helium temperatures. Here, Bradec et al. report the observation of room-temperature superradiance from single, highly luminescent diamond nanocrystals with spatial dimensions much smaller than the wavelength of light.